Microstructure Characterization of Whey Films Using Different Concentrations of Chia Seeds and 35% Sorbitol as Plasticizer - Fahrullah, Fahrullah; Kisworo, Djoko; Noersidiq, Azhary; Bulkaini, Bulkaini; Yulianto, Wahid; Wulandani, Baiq Rani Dewi; Maslami, Vebera (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
SEM testing was used to evaluate the homogeneity of the film, including pores, cracks, and surface structure, as well as to determine the cross-section and surface structure and the homogeneity of the film solution mixture. The study aims to determine the microstructure characteristics of whey film by adding different concentrations of chia seed and 35% sorbitol as a plasticizer. This study employed three treatments: P1 with 0.5% chia seed, P2 with 0.75% chia seed, and P3 with 1% chia seed. The research method used was descriptive, providing a detailed description of the process. The results indicate that adding more polymer increases the viscosity of the film suspension during the gelatinization process. The film's microstructure was determined by the heating and drying process, as well as the contribution of chia seed gel to the whey film structure. All treatments achieved a Homogeneous film microstructure, but the 1% concentration treatment resulted in a swollen surface structure. The chia seed was evenly mixed into the whey protein matrix, resulting in a uniform structure.